Mono-like silicon ingots grown on low angle misoriented seeds: Defect characterization by synchrotron X-ray diffraction imaging. (15th April 2015) - Tsoutsouva, M.G.; Oliveira, V.A.; Camel, D.; Baruchel, J.; Marie, B.; Lafford, T.A.
Abstract: The present work studies the generation and propagation of sub-grain boundaries and dislocations in mono-like silicon ingots grown on monocrystalline seeds with a very small relative misorientation between them (<0.06° around the x, y and z axes). Special emphasis is put on the region close to the area between the seeds at the bottom of the crucible, which appears to be crucial in determining the crystalline quality of the final ingot. For this investigation, X-ray rocking curve imaging (RCI) in transmission geometry, a directly quantitative version of monochromatic beam Bragg diffraction imaging ("topography") has been used. This technique has been developed at the European Synchrotron Radiation Facility (ESRF), beamline BM05 and allows us to visualize the spatial distribution of the lattice distortion of a single crystal. It was found that the solidified ingot takes the crystallographic orientation of the seeds without creating any distorted area at the interface. However, dislocation bunches having a strong screw component are generated between the seeds and propagate along the growth direction. Sub-grain boundaries above the top of the seeds, mainly composed of edge dislocations, were also observed. These have a detrimental influence on the minority carrier lifetime of the ingot, since, as is known, sub-grain boundaries show active recombination. In this work taking advantage of the high angular resolution and the sensitivity of the technique it was shown that a relative misorientation between the seeds (δ θx, δ θy, δ θz ) as small as 0.02° can produce cascades of dislocations that propagate and multiply higher up in the ingot becoming electrically active.